2017
DOI: 10.18632/oncotarget.20200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CADD522, a small molecule that inhibits RUNX2-DNA binding and exhibits antitumor activity

Abstract: The RUNX2 transcription factor promotes breast cancer growth and metastasis through interactions with a variety of cofactors that activate or repress target genes. Using a direct drug discovery approach we identified CADD522 as a small molecule that inhibits the DNA binding of the runt box domain protein, RUNX2. The current study defines the effect of CADD522 on breast cancer growth and metastasis, and addresses the mechanisms by which it exerts its anti-tumor activity.CADD522 treatment resulted in significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 107 publications
2
33
0
Order By: Relevance
“…We previously reported that the transcription factor runt-related transcription factor 2 (RUNX2) promotes glycolytic switching in BC cells by increasing expression of genes regulating glycolytic pathways [52]. RUNX2 decreases pyruvate dehydrogenase (PDH) activity but RUNX2 KD increases mitochondrial oxygen consumption rate (OCR) by increasing the activity of PDH, a rate limiting step for entry into the TCA cycle at the branch point for pyruvate utilization.…”
Section: Research Papermentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that the transcription factor runt-related transcription factor 2 (RUNX2) promotes glycolytic switching in BC cells by increasing expression of genes regulating glycolytic pathways [52]. RUNX2 decreases pyruvate dehydrogenase (PDH) activity but RUNX2 KD increases mitochondrial oxygen consumption rate (OCR) by increasing the activity of PDH, a rate limiting step for entry into the TCA cycle at the branch point for pyruvate utilization.…”
Section: Research Papermentioning
confidence: 99%
“…These findings led us to hypothesize that targeting RUNX2 might inhibit BC growth and/or progression by reversing tumor cell dependence on glycolysis. In our effort to find small molecules that target RUNX2 by interfering with RUNX2 binding to the specific DNA sequences, we used Computer-Assisted Drug Design (CADD) [52,53]. Based on this approach, CADD522 ( Supplementary Figure 2, left) was identified as a potent inhibitor of RUNX2-DNA binding [52,53].…”
Section: Research Papermentioning
confidence: 99%
See 2 more Smart Citations
“…In order to validate Runx2 regulation of MMHN genes in vitro, we cultured BMDMs and incubated them for 48 hours with 20 μM CADD522, a drug previously shown to selectively block Runx2 DNA binding activity (37). Expression of genes positively and negatively correlated with Runx2 was then assessed by quantitative reverse-transcription PCR (qRT-PCR).…”
Section: Resultsmentioning
confidence: 99%